Gratitude, resignation and the desire for dignity: lived experience of food charity recipients and their recommendations for improvement, Perth, Western Australia - Booth, S.; Begley, Andrea; Mackintosh, B.; Kerr, Deborah; Jancey, Jonine; Caraher, M.; Whelan, J.; Pollard, C. (Cambridge University Press, 2018)
Objective: The present study explored recipients’ perceptions of food charity and their suggested improvements in inner-city Perth, Western Australia. Design: In-depth interviews were conducted with charitable food service (CFS) recipients. Transcripts were thematically analysed using a phenomenological approach. Setting: Interviews were conducted at two CFS in inner-city Perth. Subjects: Fourteen adults. Results: The recipients’ journeys to a reliance on CFS were varied and multifactorial, with poverty, medical issues and homelessness common. The length of time recipients had relied on food charity ranged from 8 months to over 40 years. Most were ‘grateful yet resigned’, appreciative of any food and resigned to the poor quality, monotony and their unmet individual preferences. They wanted healthier food, more variety and better quality. Accessing services was described as a ‘full-time job’ fraught with unreliable information and transport difficulties. They called for improved information and assistance with transport. ‘Eroded dignity’ resulted from being fed without any choice and queuing for food in public places, often in a volatile environment. ‘Food memories and inclusion’ reflected a desire for commensality. Recipients suggested services offer choice and promote independence, focusing on their needs both physical and social. Conclusions: Although grateful, long-term CFS recipients described what constitutes a voluntary failure. Their service improvement recommendations can help meet their nutritional and social needs. A successful CFS provides a food service that prioritises nutritious, good-quality food and individual need, while promoting dignity and social inclusion, challenging in the current Australian context.